Should we Target Allergen Protease Activity to Decrease the Burden of Allergic Airway Inflammation? - Vliagoftis, Harissios; Forsythe, Paul (Inflammation & Allergy-Drug Targets (Discontinued), 2008)
The prevalence of allergy and asthma has been increasing steadily in the developed world. Despite the growing health problems associated with these conditions few new therapeutic options are becoming available. Relatively recent developments have identified a role for proteases in promoting allergic sensitisation and allergic airway inflammation. It is also known that most major allergens have associated protease activity that is closely related to their efficacy to induce sensitization and inflammation. Here we review the evidence for the significance of protease activity in allergic airway disease and offer suggestions as to where the field could progress.
Keywords: allergen